A Comprehensive Look at the Challenges of Mobile Banking from the Consumer’s Point of View - Zoubida, OUYAHIA; Rachid-Sofiane, TOUIL (The journal of contemporary issues in business and government, 2023)
Mobile banking is a modern and convenient banking service that has revolutionized the banking industry by providing customers with easy access to their bank accounts and a range of banking services through their mobile devices, However, the widespread adoption of mobile banking is still hindered by several challenges. This paper examines the challenges of mobile banking and the views of consumers towards mobile banking adoption. Algerian customers have a positive attitude towards mobile banking, It is attributed to its user-friendly interface, visually pleasing design, fast and efficient management and viewing of accounts, high level of security, and the availability of various features and services. In contrast to the generally positive view of mobile banking, customers have reported low satisfaction with customer service.